Pengetahuan Ibu Menyusui Pasca Edukasi Tentang Asi Eksklusif - Afrizal Rifa'i; Sri Lestari Dwi Astuti; Yuyun Setyorini ((JKG) Jurnal Keperawatan Global, 2020)
Background: Exclusive breastfeeding has important role in ensuring adequate nutrition, stunting prevention, and child development. The success rate of exclusive breastfeeding in the World is only (38%), Indonesia (65.1%), Central Java (78.5%) and the working area of ​​ Sibela Local Government Clinic of Surakarta (85.4%). Maternal's knowledge level is part of the determinants of success rates in exclusive breastfeeding. Health education is efforts used to increase maternal knowledge about exclusive breastfeeding. Methods: This research is Pre Experiment with One Group Pre-Post Test. The methode of collecting of data is accidental sampling with questionnaire who containing 20 questions. The comparative hypothesis test used Wilcoxon test. Results: from 42 respondents, 22 (52.4%) had high school education, 21 (50%) were housewives, 24 (57.1%) according to the range of early adulthood (26-35 years) and 31 (73.8%) had got education about exclusive breastfeeding from health workers. The comparative hypothesis test results show a significance 0,00 (p value <0.05). Conclusion: There is an effect of health education about exclusive breastfeeding on the knowledge of breastfeeding maternal in the Sibela Local Government Clinic of Surakarta.